Determination of diagnostic reference levels (drls) for digital radiography (abdomen & pelvic examinations) in Hospital Universiti Sains Malaysia (HUSM) - Zain, Shafirah Mohd (Universiti Sains Malaysia, 2016)
The aim of this study is measurement the diagnostic reference levels (DRLs) for digital radiography (abdomen & pelvic examinations) in Hospital USM. This study is the estimation of the entrance surface dose (ESD) delivered to patients. ESD can be measured directly by using Thermoluminescence Dosimeter (TLD) which is LiF: Mg,Cu,P (TLD 100H). The examination involved 30 patients for each procedures of abdomen (AP) and pelvic (AP). The participants involved in range 18 years old and above, weight between 35 to 100 kg, and both male and female are included. The ESD were measured directly with TLD 100H that mounted on tape and placed at the centre x-ray beam on patient skin. The DRLs value found in Hospital USM were compared to DRLs stated by national and international. Hospital USM third quartile of ESDs value estimated for abdomen is 3.75 mGy and pelvic is 2.75 mGy. This result indicate that the ESD received by patients were to be lowered than or in acceptance range with the guidance level set by the national, IAEA and other international country. One possible reason is that the patient size is relatively smaller than a European patient. It is also possible that x-ray machine at Hospital USM was well maintained and have pass all the annual Quality Assurance evaluations before being operate. Consequently, the radiation risk to patients is minimized and will help in optimization radiation protection of patient. Overall it was found this result will be useful for the formulation of reference in HUSM as recommended by the IAEA.